Prediction of multiphase flow in pipelines: literature review (2015)
In this work a review about the most relevant methods found in the literature to model the multiphase flow in pipelines is presented -- It includes the traditional simplified and mechanistic models, moreover, principles of the drift flux model and the two fluid model are explained -- Even though, it is possible to find several models in the literature, no one is able to reproduce all flow conditions presented in the oil industry -- Therefore, some issues reported by different authors related to model validation are here also discussed